Management of cumin blight by novel fungicides: A menacing disease of south-western Rajasthan - SHARMA, JITENDAR KUMAR; SHARMA, KAPIL; SHEKHAWAT, H V S; JOSHI, NEESHU; MEENA, VIJAY KAMAL; LEKHA; CHOUDHARY, ANIRUDH (The Indian Journal of Agricultural Sciences, 2024)
A study was carried out during winter (rabi) seasons of 2019–20 and 2020–21 at Agricultural Research Sub-station (Agriculture University, Jodhpur), Sumerpur, Pali, Rajasthan to find out the best novel fungicide for management of cumin blight. The experiment was laid out in a randomized block design (RBD) comprised of 10 treatments i.e. Four fungicides, combination of Pyraclostrobin 133 g/litre + Epoxiconazole 50 g/litre (500 and 750 ml/ha), Tebuconazole 25% wg (500 and 750 g/ha), Azoxystrobin 23% sc (500 and 750 ml/ha) and Thiophanate-methyl 70% wp (750 and 1000 g/ha) in two different concentrations and one check (Mancozeb 75% wp @1000 g/ha) and one un-treated control, replicated thrice. The susceptible variety GC-4 (Gujarat cumin-4) of cumin (Cuminum cyminum L.) was used for the experiment. The in vivo study recorded variable sensitivity of different fungi-toxicants against cumin blight pathogen. Among the different fungi-toxicants, Tebuconazole 25% wg @750 g/ha, was found highly efficacious by observing lowest per cent disease intensity (8.89% and 12.11%) at 15 days after first foliar spray and 15 days after second foliar spray respectively and maximum yield (645 kg/ha). The combination of Pyraclostrobin 133 g/litre + Epoxiconazole 50 g/litre @750 ml/ha and Tebuconazole 25% wg @500 g/ha also found effective in controlling the cumin blight. While Azoxystrobin 23% sc @500 and 750 g/ha, Thiophanate-methyl 70% wp @750 and 1000 g/ha and Mancozeb 75% wp @1000 g/ha were found least effective.